Management of Hypervolemia In Chronic Kidney Disease Stage 5 At Sumedang Hospital: A Case Study - Annisa Nurbaiti Rahmah; Eka Afrima Sari; Nita Fitria (Universitas Padjadjaran, 2022)
Kidney failure results in the body being unable to remove metabolic wastes and accumulate in the body. Decreased kidney function results in sodium retention, where high sodium will cause water to be retained to maintain balance. This can lead to hypervolemia. Patient M came to the hospital with complaints of shortness of breath, during the study, there was edema in both lower extremities with degree 2 and in both upper extremities with degree 1, the patient also appeared to have ascites. Previously, patient M was diagnosed with stage 5 chronic kidney failure and did not complete the 4th hemodialysis cycle because the patient's condition worsened. Hypervolemia in patients with kidney failure will have adverse effects including pulmonary edema, hypertension, and even heart disease. Therefore it is necessary to manage hypervolemia to prevent complications in patients. The general aim of writing this case study is to address the management of hypervolemia in stage 5 chronic kidney failure patients at the Sumedang Regional General Hospital. The results of the case study found that the nursing problem that arose in patients was hypervolemia. The interventions provided are managing hypervolemia in the form of examining signs and symptoms of hypervolemia, monitoring the patient's hemodynamic status, monitoring the patient's fluid intake and output, teaching the patient to limit fluid and salt intake, and collaborating with Lasix 1x40 mg. Evaluation results after managing hypervolemia for 3 days, decreased tightness, degree of edema remained at degree 2 in the lower extremities and upper extremities, increased abdominal circumference by 1 cm, and increased body weight from 0.5 Kg to 68.5 kg, it can be concluded that hypervolemia nursing problem has not been resolved.